Invisibilitas Hak Maternitas Pekerja Perempuan Perjanjian Kerja Waktu Tertentu (PKWT) dalam Sistem Ketenagakerjaan: Studi Sosio-Legal - Nuril F Lamawatu (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2026)
Amidst the dominance of flexible employment relationships in the manufacturing sector, women workers with Fixed-Term Employment Agreements (Perjanjian Kerja Waktu Tertentu/PKWT) face double vulnerability: job insecurity and marginalization in the context of reproductive rights. This research aims to analyze the extent to which legal norms and social realities are aligned in relation to the fulfillment of the maternity rights of women PKWT workers in labor-intensive industries. It uses a descriptive qualitative method with a socio-legal and worker welfare approach. Primary data was obtained through in-depth interviews with three women workers. The number of respondents was intended to explore personal experiences in depth, not to generalize the population. Secondary data refers to legislation, academic literature, and academic policies, which were then analyzed thematically and comparatively with empirical findings. The results of the study show that the fulfillment of maternity rights is still partial and uneven—even for workers with formal status as PKWT. The conditions of these workers are more similar to those of casual daily workers with attendance-based wages, uncertain contracts, and limited access to maternity rights. This condition demonstrates a discrepancy between statutory labour protection and its implementation at the workplace level. This research argues that strengthening labour supervision, improving complaint mechanisms, and ensuring effective enforcement of maternity protection are necessary to protect women workers, particularly those in fixed-term and other non-standard employment arrangements.